Ventilatory Care in Status Asthmaticus - Robert J Smyth (Canadian Respiratory Journal)
Asthma continues to pose a significant medical problem in terms of both morbidity and mortality. A number of patients with a severe exacerbation of asthma fail medical therapy and require urgent intubation and mechanical ventilation. New modalities of ventilatory support, including noninvasive ventilation, have been shown to provide effective ventilation even in the presence of severe bronchoconstriction. An intrinsically high level of auto positive end-expiratory pressure in these patients requires a precise balance between respiratory frequency, tidal volume and inspiratory flow rates. Pressure support ventilation reduces the risk of barotrauma and lowers the work of breathing in these patients. Adjuvant therapy with inhaled anesthetics and bronchoalveolar lavage may also be indicated in patients requiring high pressures to achieve adequate ventilation.